Marketing Relations Performance Behavior in Regional Office Palembang in Value Chain Based Credit Initiative - William, Maradong Enrico; Irsan, Arully; Raharjo, Susilo Toto; Wibawa, Kadek Cahya Susila (LifeSciFi, 2024)
Value Chain Financing (VCF) is a financing solution through financial instruments, practices, and technology to optimize the management of working capital and liquidity related to the value chain process for the parent company and supplier companies, distributors, or agents as end users. By utilizing data effectively, Bank BRI can improve financial performance, strengthen competitive positions, and provide added value to customers. For marketing staff at Bank BRI in Regional Office Palembang, especially in the context of the retail loan business, this database has a crucial role in creating strategies to improve performance in credit initiatives based on the Value Chain database. In the context of the retail loan business at Bank BRI, the value chain database has an important role in improving efficiency, effectiveness, and service quality. This study uses a qualitative approach to explore and understand the behavior of marketing performance at Regional Office Palembang in carrying out value chain-based credit initiatives. The purpose of this study is to find out how the Value Chain Database can help the performance of Marketing Staff at Bank BRI in Regional Office Palembang to be even better. So that these Marketing Staff can formulate strategies to improve marketing performance supported by Value Chain-based credit initiatives